2022
DOI: 10.1002/cphc.202200053
|View full text |Cite
|
Sign up to set email alerts
|

Can Water Act as a Nucleophile in CO Oxidation Catalysed by Mo/Cu CO‐Dehydrogenase? Answers from Theory

Abstract: The aerobic CO dehydrogenase from Oligotropha carboxidovorans is an environmentally crucial bacterial enzyme for maintenance of subtoxic concentration of CO in the lower atmosphere, as it allows for the oxidation of CO to CO2 which takes place at its Mo−Cu heterobimetallic active site. Despite extensive experimental and theoretical efforts, significant uncertainties still concern the reaction mechanism for the CO oxidation. In this work, we used the hybrid quantum mechanical/molecular mechanical approach to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…We have not been able to obtain any stable species in which the CO molecule is close to the Cu ion, without being bound to it, allowing CO oxidation through a frustrated Lewis pair (FLP) mechanism, as suggested recently. 23 Thus, our calculations give no support to a FLP mechanism for CO oxidation, in contrast to what was suggested for H 2 oxidation 24 (another interesting reactivity expressed by Mo/Cu-CODH).…”
Section: ■ Results and Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…We have not been able to obtain any stable species in which the CO molecule is close to the Cu ion, without being bound to it, allowing CO oxidation through a frustrated Lewis pair (FLP) mechanism, as suggested recently. 23 Thus, our calculations give no support to a FLP mechanism for CO oxidation, in contrast to what was suggested for H 2 oxidation 24 (another interesting reactivity expressed by Mo/Cu-CODH).…”
Section: ■ Results and Discussioncontrasting
confidence: 92%
“…The catalytic mechanism reported here contemplates the formation of the new C–O bond by direct involvement of the catalytically labile oxo ligand of Mo, which was recently evidenced to be the only nucleophile able to promote such a bond-making reaction in Mo/Cu-CODH . The most difficult proposal to be incorporated into the catalytic cycle was the presence of a thiocarbonate intermediate, IntD , in the reaction path.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49][50] On the basis of the structure of inhibitor n-butyl isocyanide (t-BuNC or CNÀ R) bound CODH complex and in addition to computational studies, the proposed reaction mechanism of oxidation of CO by cofactor is shown in Figure 2. [43,44,46,[48][49][50][51][52][53][54] The bridged sulfide ligand directly participates in the formation of thiocarbonate and is proposed to be an intermediate state for the oxidation of CO in the catalytic cycle. [5,48] In CNÀ R bound structure, no MoÀ SÀ Cu link is observed but thiocarbamate ligand coordinates to Mo by S and O sites and to Cu by N site, thereby Cu site is moving away from the Mo site (Figure 2; A-Cycle).…”
Section: Codh Activity Of the Moà Cuà Codhmentioning
confidence: 99%
“…All calculations were performed within the framework of density functional theory (DFT) at the BP86-D3(BJ)/def2-TZVP level, [15][16][17][18] an approach which already proved successful for the modelling of Mo complexes in the presence of oxo and sulphide ligands. [19][20][21][22] Calibration of the method employed was also assessed by testing different DFT functionals and basis sets as reported in Table S2 in the Supplementary Information. Geometry optimizations of all models were carried out both in a vacuum and in a water-like solvent, described by the conductor-like polarizable continuum model (C-PCM).…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%